Pathophysiological aspects of red blood cells in end‐stage renal disease patients resistant to recombinant human erythropoietin therapy. (12th April 2017) - Georgatzakou, Hara T.; Tzounakas, Vassilis L.; Kriebardis, Anastasios G.; Velentzas, Athanassios D.; Papageorgiou, Effie G.; Voulgaridou, Artemis I.; Kokkalis, Apostolos C.; Antonelou, Marianna H.; Papassideri, Issidora S.
Abstract: Objective: Modified, bioreactive red blood cells (RBCs) and RBC‐derived microvesicles (MVs) likely contribute to the hematological and cardiovascular complications in end‐stage renal disease (ESRD). This study assesses the physiological profile of RBCs in patients with ESRD receiving standard or high doses of recombinant human erythropoietin (rhEPO). Method: Blood samples from twenty‐eight patients under sustained hemodialysis, responsive, or not to standard rhEPO administration were examined for RBC morphology, fragility, hemolysis, redox status, removal signaling, membrane protein composition, and microvesiculation before and after dialysis. Acute effects of uremic plasma on RBC features were examined in vitro through reconstitution experiments. Results: Overall, the ESRD RBCs were characterized by pathological levels of shape distortions, surface removal signaling, and membrane exovesiculation, but reduced fragility compared to healthy RBCs. Irreversible transformation of RBCs was found to be a function of baseline Hb concentration. The more toxic uremic context in non‐responsive patients compared to rhEPO responders was blunted in part by the antioxidant, antihemolytic, and anti‐apoptotic effects of high rhEPO doses, and probably, of serum uric acid. A selective lower expression of RBC membrane in complement regulators (CD59, clusterin) and of CD47 "marker‐of‐self" was detected in non‐responders and responders, respectively. Evidence for different short‐term dialysis effects and probably for a different erythrocyte vesiculation mechanism in rhEPO responsive compared to non‐responsive patients was also revealed. Conclusion: Deregulation of RBC homeostasis might involve diverse molecular pathways driving erythrocyte signaling and removal in rhEPO non‐responders compared to responsive patients.